Development of mathematical relation between ESDD and wind velocity for a contaminated insulator in Malaysia - Abdus Salam, M.; Ahmad, H; Fuad, S.A; Ahmad, A.S; Tamsir, T; Piah, M.A.M; Buntat, Z; Saadom, Zulkiply; Budin, Razali (2000)

(untitled)
Insulator contamination has been identified as the most important design parameter for external insulation of the high voltage network systems. Wind and electrostatic field plays an important role in transporting and depositing of that contamination over the insulator surface. This contamination severity on the insulator surface can be expressed and represented by Equivalent Salt Deposit Density (ESDD). The values of ESDD can be determined easily through a closed form of mathematical relation. In this paper, a mathematical relation between ESDD, wind velocity and leakage distance of the insulator has been proposed using Dimensional Analysis technique. The results obtained from this analytical expression have been compared with the practical data, which are collected from the Paka Thermal Power Station and good agreement are observed at lower wind velocity